2006
DOI: 10.1080/09243860600707447
|View full text |Cite
|
Sign up to set email alerts
|

Influence of high-calorie (cafeteria) diets on the population of Paneth cells in the small intestine of the rat

Abstract: A high-calorie (cafeteria) diet is known to cause changes in the intestinal morphology and functioning that seem to be related to calorie overfeeding. Among the cell lineages found in the small intestine epithelium, the Paneth cell (PC) population is known to be influenced by factors related mainly to the intestinal microbiota. The role of PCs in the intestinal cell concert remains unclear, because experimental evidence suggests PC involvement in local processes other than protection against pathogens. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…They respond to neuronal stimulation, modulate microbiota and are impacted by the flora, oppose the NEC phenotype, sustain a healthy restitutive stem cell niche and develop in par with the gut (Lueschow and McElroy, 2020). Paneth cell number has been correlated to diet such that the Paneth cell numbers in the small intestine decrease following excessive intake of diets laden with fat and carbohydrates (Becerril et al, 2005). With a turnover time of about 15 days (Karam, 1999), these cells are a potential target for orally consumed medicinal plants and phytochemicals which can alter their function and developmental trajectory.…”
Section: Paneth Cells As Phytomedicinal Intermediaries In Gut Maturationmentioning
confidence: 99%
“…They respond to neuronal stimulation, modulate microbiota and are impacted by the flora, oppose the NEC phenotype, sustain a healthy restitutive stem cell niche and develop in par with the gut (Lueschow and McElroy, 2020). Paneth cell number has been correlated to diet such that the Paneth cell numbers in the small intestine decrease following excessive intake of diets laden with fat and carbohydrates (Becerril et al, 2005). With a turnover time of about 15 days (Karam, 1999), these cells are a potential target for orally consumed medicinal plants and phytochemicals which can alter their function and developmental trajectory.…”
Section: Paneth Cells As Phytomedicinal Intermediaries In Gut Maturationmentioning
confidence: 99%
“…We previously reported that α-defensin, secreted in the lumen of the mouse intestine, is highest in the ileum, where the number of intestinal bacteria increases dramatically, as well as in the duodenum and jejunum, where food digestion and absorption occur [11]. Additionally, a correlation between Paneth cell number and diet has been reported; the number of Paneth cells in the duodenum and jejunum decreases following excessive calorie intake (diet rich in carbohydrate and fat) [12]. Paneth cells are known to form a stem cell niche [13] and enhance stem cell function in response to calorie limitations [14,15].…”
Section: Introductionmentioning
confidence: 99%